A Case Report of Simultaneous Hypotensive Patients Managed with Concurrent REBOA in a Single-Surgeon Austere Combat Casualty Environment - Manley, Justin D; Le, Alexander T; Nam, Jason J (Journal of Endovascular Resuscitation and Trauma Management, 2018)
Current trends in combat damage control resuscitation (DCR) and damage control surgery (DCS) are moving toward increased support and utilization of resuscitative endovascular balloon occlusion of the aorta (REBOA). The initial reports of successful utilization in combat casualty care, spearheaded by the development of the smaller Prytime ER-REBOA™ catheter, have helped to drive further investment into expanding the use of REBOA. We present a case report that highlights the multiple benefits of REBOA in DCR and DCS. This case report involves the simultaneous management of two combat casualties with non-compressible torso hemorrhage (NCTH) and hypotension. Concurrent use of REBOA in this situation, where both patients required immediate surgery with only one surgeon and operating room table available, emphasizes that REBOA use provides temporization of immediately life-threatening NCTH, a relatively dry operative field, reduced time to operative hemorrhage control, and decreased use of blood products.